2006
DOI: 10.1158/0008-5472.can-05-4154
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Analysis of Chromosomal Breakpoints and Genomic Instability Identifies PTPRD as a Candidate Tumor Suppressor Gene in Neuroblastoma

Abstract: Although neuroblastoma is characterized by numerous recurrent, large-scale chromosomal imbalances, the genes targeted by such imbalances have remained elusive. We have applied whole-genome oligonucleotide array comparative genomic hybridization (median probe spacing 6 kb) to 56 neuroblastoma tumors and cell lines to identify genes involved with disease pathogenesis. This set of tumors was selected for having either 11q loss or MYCN amplification, abnormalities that define the two most common genetic subtypes o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
102
1

Year Published

2006
2006
2008
2008

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 116 publications
(116 citation statements)
references
References 29 publications
13
102
1
Order By: Relevance
“…4,5,14,53 A number of highly coamplified regions that were discontinuous regarding the MYCN locus and located at varying distances from MYCN were described, demonstrating the unique constitution of the MYCN amplicon. 4,5,14,53 Interestingly, only one group of researchers found high-level amplification of two genes (SNTG2 and TPO) situated at 936 kb and 1.4 Mb, respectively, from 2pter, occurring in one of 10 MNA samples.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,14,53 A number of highly coamplified regions that were discontinuous regarding the MYCN locus and located at varying distances from MYCN were described, demonstrating the unique constitution of the MYCN amplicon. 4,5,14,53 Interestingly, only one group of researchers found high-level amplification of two genes (SNTG2 and TPO) situated at 936 kb and 1.4 Mb, respectively, from 2pter, occurring in one of 10 MNA samples.…”
Section: Discussionmentioning
confidence: 99%
“…The region of 1p loss is quite large, containing many potential candidate genes. Furthermore, smaller homozygous deletions that might further pinpoint the genes of interest are exceedingly rare Stallings et al, 2006) and do not define a single shortest region of overlap (Schleiermacher et al, 1994). Expression microarray studies of primary tumors have also led some investigators to suggest that multiple genes on chromosome 1p contribute to NB pathogenesis (Janoueix-Lerosey et al, 2004;Wang et al, 2006), a concept supported by the fact that in vitro functional studies have shown that more than one gene from chromosome 1p can have anti-tumorigenic effects when ectopically expressed in NB cell lines (Ejeskar et al, 2005;Valentijn et al, 2005).…”
mentioning
confidence: 99%
“…For example, two miRNAs (miR-15 and miR-16) mapping to chromosomal region 13q14 are frequently deleted and downregulated in chronic lymphocytic leukemia and thus act as tumor suppressor genes (Calin et al, 2002). MiRNAs acting in a dominant oncogenic manner are illustrated by miR-21 on chromosome 17q, which, when overexpressed in some forms of cancer have anti Figure 1 Analysis of 1p loss in 13 primary tumors and the SK-N-AS cell line using oligonucleotide array CGH, as described previously (Stallings et al, 2006). The vertical axis of each plot represents the fluorescence ratio of tumor to normal DNA on a log 2 scale, whereas the horizontal axis represents genomic position on chromosome 1p in base pairs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…to study DNA alterations on a genome-wide scale, including array CGH with very high genome resolution [4], new methylation detection systems [5], and last but not least, single-molecule sequencing technologies [6] (Box 1). In this review we focus on the recent biological discoveries that have been made with these new tools along with the large-scale efforts using older tools.…”
Section: Introductionmentioning
confidence: 99%